2001
DOI: 10.1093/gerona/56.9.b384
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training Reduces Susceptibility to Eccentric Exercise-Induced Muscle Dysfunction in Older Women

Abstract: This study evaluated the effect of age on susceptibility to muscular weakness and damage caused by eccentric (ECC) exercise and determined whether this susceptibility was altered by resistance training. Young and older women performed concentric (CON) and ECC one repetition maximum (1 RM) strength tests of the quadriceps femoris. Older women also performed knee extension training for 12 weeks. An unaccustomed bout of ECC knee extension exercise was performed before and after training, and CON and ECC 1 RM were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
61
3
8

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 28 publications
4
61
3
8
Order By: Relevance
“…This method has not been validated against histological assessment of muscle damage, and data are not available regarding the relationship between the relative area demonstrating an increase in T2 and other indirect markers of injury (likely because of small sample sizes). Nevertheless, data from previous studies (6,7,31,34,35,40) are consistent with our finding that, as the area with an elevated T2 increases, concurrent increases are observed in strength loss, swelling, and soreness. Further studies are needed to determine the mechanism(s) underlying the delayed increase in T2 signal intensity and to compare the pixel-by-pixel analysis with ultrastructural changes consistent with muscle injury.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This method has not been validated against histological assessment of muscle damage, and data are not available regarding the relationship between the relative area demonstrating an increase in T2 and other indirect markers of injury (likely because of small sample sizes). Nevertheless, data from previous studies (6,7,31,34,35,40) are consistent with our finding that, as the area with an elevated T2 increases, concurrent increases are observed in strength loss, swelling, and soreness. Further studies are needed to determine the mechanism(s) underlying the delayed increase in T2 signal intensity and to compare the pixel-by-pixel analysis with ultrastructural changes consistent with muscle injury.…”
supporting
confidence: 93%
“…MRI is especially useful for studying muscle injury in vivo because it is noninvasive and allows for spatial localization of injury to individual muscles. The pixel-by-pixel analysis employed in the present study has been used in several previous studies (6,7,31,34,35,40) and is thought to provide a quantitative index of the relative extent and pattern of muscle injury (31). This method has not been validated against histological assessment of muscle damage, and data are not available regarding the relationship between the relative area demonstrating an increase in T2 and other indirect markers of injury (likely because of small sample sizes).…”
mentioning
confidence: 99%
“…The researchers noted, however, that the older participants in their study were very active, regularly participating in sport, exercise, or strenuous work. In support of this finding, Ploutz-Snyder et al (2001) resistance-trained a group of older women (63 ± 5 years) for 12 weeks and reported that after the training intervention, these women displayed no difference from younger untrained women (23 ± 4 years old) in muscle damage after a series of lengthening contractions as indicated by magnetic resonance imaging and loss of strength. Similarly, it has been recently reported (Fell, Haseler, Gaffney, Reaburn, & Harrison, 2006) that after a 30-min cycling time trial, serum CK concentrations increased in young and veteran endurance athletes matched for training load.…”
Section: Greater Exercise-induced Skeletal-muscle Damagementioning
confidence: 82%
“…Few studies, however, have investigated the susceptibility of muscles of older humans to exerciseinduced muscle damage. In studies that have used humans, there have been conflicting findings, with some studies reporting significant age-related differences in exerciseinduced muscle damage (Manfredi et al, 1991;Ploutz-Snyder, Giamis, Formikell, & Rosenbaum, 2001;Roth et al, 2000), whereas other studies report no differences in muscle damage between young and older participants when assessed by decreases in isometric force (Clarkson & Dedrick, 1988) or via electron microscopy (Roth et al, 1999). In a recent study that attempted to address these incongruous findings, Lavender and Nosaka (2006a) compared indirect markers of muscle damage, such as change in muscle force and range of movement and perceived soreness, after lengthening contractions of the elbow flexors in young (19.4 ± 1.3 years) and older (70.5 ± 4.7 years) men.…”
Section: Greater Exercise-induced Skeletal-muscle Damagementioning
confidence: 99%
“…Injury is more likely to occur, and muscle regeneration is delayed in skeletal muscle of elderly humans/animals compared with young humans/animals (16,17,56,60,96,97,100,101,117,119,120,173). Evidence is accumulating that rapid and efficient repair of muscle injury requires a well-coordinated and tightly controlled inflammatory response (4,56,135,140,143,150,(161)(162)(163).…”
mentioning
confidence: 99%